(untitled) (Global Journal of Medical Research, 2023)
Non-Hodgkins lymphomas are malignant lymphatic tumors mainly affecting B cells Generally occur in children and young adults with different forms of treatment however most treatments are accompanied by tumoral relapse Recently many researches have been made to identify the best treatment with positive long-term outcomes In that regard CAR-T cell treatment has been recognized for its accessibility and effect it utilizes T cells with chimeric antigen receptors facilitating cancerous cells detection after non-response to the regular R-CHOP treatment As data-base 26 research papers were found with 23 of them being utilized